(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article analyzes the importance of modern computer technologies and artificial intelligence (AI) systems in the field of pediatric cardiology, their role in medical diagnostics, treatment and prevention. The achievements of artificial intelligence in early detection of heart diseases, real-time monitoring of the patient’s condition, creation of a heart model using "digital twin" technology are highlighted. The article compares and analyzes foreign and domestic experiences